2020
DOI: 10.1186/s12889-020-08547-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between iodine intake and semen quality among fertile men in China

Abstract: Background: Iodine intake is essential in the production of thyroid hormone but very few foods are rich in it. Iodine deficiency or excess iodine level may both lead to thyroid disorders, which further affects human fertility function. The objective of this study is to investigate the relationship between iodine intake and seminal parameters among fertile men in China. Methods: A total of 1098 couples were recruited by trained physicians at different family planning service stations in 2015. Semen and iodine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Iodine is also an essential micronutrient for the thyroid gland to synthesize thyroid hormones ( 39 ). Previous studies have identified that both iodine deficiency and iodine excess may lead to thyroid dysfunction ( 40 , 41 ). Thus, we carried out subgroup analyses stratified by urine iodine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine is also an essential micronutrient for the thyroid gland to synthesize thyroid hormones ( 39 ). Previous studies have identified that both iodine deficiency and iodine excess may lead to thyroid dysfunction ( 40 , 41 ). Thus, we carried out subgroup analyses stratified by urine iodine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Our results lend, in part, credence to those of Lotti et al [ 31 ], who found that the euthyroid subjects ( n = 145) had lower semen volumes compared to those with subclinical hyperthyroidism ( n = 6) and higher than those with subclinical hypothyroidism ( n = 12); however, no association of the semen parameters with TSH was noted. In a large ( n = 1098) study from China, suboptimal or excessive dietary iodine intake was associated with a slightly lower semen volume compared to the optimal dietary iodine intake; however, the authors did not present the thyroid function status [ 32 ]. The most prominent effect of thyroid function abnormalities on semen parameters seems to be on impaired motility [ 33 , 34 , 35 ] and/or morphology [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism, whether subclinical or overt, has been linked to an increased risk of coronary artery disease. This is thought to be due to the effects of low thyroid hormone levels on lipid metabolism and vascular function [27]. Insulin resistance is a condition related to glucose regulation, in which the response of the liver, muscle, adipose tissue, and other body tissues to insulin is less than what is expected [28].…”
Section: Table 4 Statistics Output Of Roc Analysis Of Markers Between...mentioning
confidence: 99%